The Legal Force of The Job Creation Law In Conditional Unconstitutional Status After The Constitutional Court Decision - Christabella Gunawan (Journal Research of Social Science, Economics, and Management, 2023)
The Job Creation Law is not only referred to as a law that has gone viral in various circles since it was enacted in 2020, it seems that the Job Creation Law continues to be a major star in the world of the Plenary State arena. Various kinds of arguments, assumptions, pros and cons emerged and during the ratification, demonstrations were inevitable. The research uses normative legal methods related to literature studies and the latest news data with a philosophical approach or ideal values. The conclusion is that the Job Creation Law is still valid and has legal force even if it is stated to be formally flawed, where material defects are a certainty. The binding legal force of the Job Creation Law lasted for two years and there was no update on the implementation of the Job Creation Law.